2009
DOI: 10.1021/la9035437
|View full text |Cite
|
Sign up to set email alerts
|

Autophilic Effect: Wetting of Hydrophobic Surfaces by Surfactant Solutions

Abstract: This paper resolves questions in the literature regarding the autophilic effect (i.e., movement of surfactant past the advancing contact line-leading to an increase in drop radius beyond that due to the advance) and its importance to quasi-static sessile drop wetting. Various systems (SDS, HTAB, and MEGA 10 surfactant solutions at three concentrations each and pure water and ethylene glycol on hydrophobic Teflon and OTS-coated silicon) are probed to determine the existence, time constant, and magnitude of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
2
22
0
1
Order By: Relevance
“…Ivanova et al [38] examined the spreading of SDS solution on the PTFE-AF coated wafer surface and reported that the change of droplet volume caused by evaporation during the whole spreading process was around 5% [38]. Milne and Amirfazli studied the system of spreading SDS solution drop on TEFLON-AF spin-coated smooth silicon wafer, using the quasi-static sessile drop technique and reported that there was no SDS surfactant adsorption on the solid-vapor interface ahead of the contact line on the first advance over the clean hydrophobic surface, and also there was no autophilic effect (i.e., movement of surfactant past the advancing contact line, leading to an increase in drop radius beyond that due to the advance) although drop spreading occurs after the volume increase of the SDS solution drops stopped during the advancing contact angle measurements within 20 s and the time for spreading is independent of SDS concentration [39].…”
Section: Adsorption Of Sds At Water-air and Solid-water Interfacesmentioning
confidence: 98%
See 1 more Smart Citation
“…Ivanova et al [38] examined the spreading of SDS solution on the PTFE-AF coated wafer surface and reported that the change of droplet volume caused by evaporation during the whole spreading process was around 5% [38]. Milne and Amirfazli studied the system of spreading SDS solution drop on TEFLON-AF spin-coated smooth silicon wafer, using the quasi-static sessile drop technique and reported that there was no SDS surfactant adsorption on the solid-vapor interface ahead of the contact line on the first advance over the clean hydrophobic surface, and also there was no autophilic effect (i.e., movement of surfactant past the advancing contact line, leading to an increase in drop radius beyond that due to the advance) although drop spreading occurs after the volume increase of the SDS solution drops stopped during the advancing contact angle measurements within 20 s and the time for spreading is independent of SDS concentration [39].…”
Section: Adsorption Of Sds At Water-air and Solid-water Interfacesmentioning
confidence: 98%
“…There is no previous publication of the SDS adsorption on TEF-LON-FEP surface, however conflicting reports were published on the SDS adsorption and spreading on fluorocarbon polymer surfaces in the literature [36][37][38][39]. Starov et al found a 3-5% increase of the contact radius, r b of the SDS solution drops on polytetrafluoroethylene (PTFE) surface within 10 s for SDS concentrations below cmc [36].…”
Section: Adsorption Of Sds At Water-air and Solid-water Interfacesmentioning
confidence: 99%
“…Since in investigated conditions pollution from CTAB or similar artificial surfactants is negligible, an indirect mechanism driven by naturally present organic matter is more likely involved. In particular, it is referred to phenomena like the autophilic effect reported by some authors, accounting for alternative changes in composition by adsorption from water-air to solid interface [51,52]. In addition, it is pointed out that CA measurement represents the status of the surface after exposure to the natural seawater environment, undergoing the effects of DOM sedimentation and accumulation implying possible macroscopic changes in the interface composition.…”
Section: Samples With Superhydrophobic Coatingmentioning
confidence: 99%
“…6 Surfactants adsorb onto the liquid vapor (LV) and solidliquid (SL) interface; adsorption onto the solidvapor (SV) interface is still under debate. 7,8 The dynamic wetting of surfactant solutions on hydrophobic solids has been mostly studied through drop-spreading 9,10 and spontaneous capillary-filling experiments. 11,12 In the latter category of experiments, penetration of surfactant solutions into hydrophobic capillaries showed different kinetic regimes.…”
mentioning
confidence: 99%